Improving Documentation Using a Real-Time Location System in a Pediatric Emergency Department - Overmann, Kevin M.; Barrick, Lindsey; Porter, Stephen C. (Applied Clinical Informatics, 2021)
Background Appropriate documentation of critical care services, including key time-based parameters, is critical to accurate severity of illness metrics and proper reimbursement. Documentation of time-based elements for critical care services performed in emergency departments (ED) remains inconsistent. We integrated electronic medical record and real-time location system (RTLS)-derived data to augment quality improvement methodology.Objective We aimed to increase the proportion of patient encounters with critical care services performed at a pediatric ED that had appropriate documentation from a baseline of 76 to 90% within 6 weeks.Methods The team formulated a framework of improvement and performed multiple plan-do-study-act cycles focused on key drivers. We integrated the capabilities of an RTLS for precise location tracking to identify patient encounters in which critical care services were performed and to minimize unnecessary audits and feedback. We developed an intervention using iterative revisions to address key drivers and improve documentation. The primary outcome was the proportion of patient encounters for which critical care services were performed for which a time-based attestation was documented in the medical record.Results We analyzed 92 encounters between March 2020 and April 2020. While the proportion of eligible patient encounters with critical care documentation improved from 76 to 85%, this change was unable to be directly attributed to improvement efforts. Patients with respiratory complaints encompassed the majority of eligible encounters without appropriate documentation.Conclusion Utilizing improvement methodology and a novel application of RTLS, we successfully identified the co-location of physicians with patients receiving critical care services and designed interventions to improve documentation of critical care services provided in a pediatric ED. While changes were not able to be attributed to improvement efforts in this project, this project demonstrates the utility of RTLS to augment and inform systematic improvement efforts.
Keywords: geographical information systems; clinical documentation; billing; emergency